Pengaruh Efikasi Diri dan Lingkungan Kerja Terhadap Kinerja di Apotek Ating Grup - Faishal Sholahudin Tirta Sasmita; Rusman Frendika (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Ating Group Pharmacy is a company engaged in the provision of health medicines for the community which has been operating for 30 years, starting in 1990 with the current number of human resources of 30 employees. Job satisfaction is a problem that occurs at the Ating Group Pharmacy, employees feel dissatisfied because they are treated less wisely and outside their field of work which creates a feeling of discomfort with each other, especially with other employees who have been in the category of having worked for a long time at the Pharmacy. Employees feel alienated by old employees in any situation and condition. Based on this statement, the problems are formulated as follows: (1) How is the self-efficacy of the employees at Ating Group Pharmacy? (2) How is the working environment at Ating Group Pharmacy? (3) How is the job satisfaction of employees at Ating Group Pharmacy? (4) How big is the effect of self-efficacy on job satisfaction at Ating Group Pharmacy? (5) How much influence does the work environment have on job satisfaction at Ating Group Pharmacy? (6) How much influence does self-efficacy and work environment have on job satisfaction at Ating Group Pharmacy? Researchers used the method of frequency analysis techniques using a quantitative approach. The population selected in this study is the total number of employees totaling 30 employees. With the sampling technique using saturated sampling or commonly called the census technique, which is one part of the non-probability total sampling technique, there are 30 respondents, which means that they are counted as a whole. Data collection techniques used in this study were questionnaires, interviews, observation, and literature study. Abstrak. Apotek Ating Group merupakan perusahaan yang bergerak di bidang penyedia obat-obatan kesehatan bagi masyarakat yang sudah bergerak sejak 30 tahun lamanya yang dimulai di tahun 1990 dengan memiliki jumlah sumber daya manusia saat ini sebanyak 30 karyawan. Kepuasan kerja menjadi permasalahan yang terjadi di Apotek Ating Group, karyawan dirasa kurang puas karena diperlakukan kurang bijak dan diluar bidang pekerjaan mereka yang menumbuhkan rasa ketidaknyaman satu sama lain terutama dengan karyawan lagi namun yang memiliki kategori telah lama bekerja di Apotek. Karyawan merasa diasingkan oleh karyawan lama dalam situasi dan kondisi apapun. Berdasarkan pernyataan tersebut maka dirumuskan masalah sebagai berikut: (1) Bagaimana efikasi diri karyawan di Apotek Ating Group? (2) Bagaimana lingkungan kerja di Apotek Ating Group? (3) Bagaimana kepuasan kerja karyawan di Apotek Ating Group? (4) Seberapa besar pengaruh efikasi diri terhadap kepuasan kerja di Apotek Ating Group? (5) Seberapa besar pengaruh lingkungan kerja terhadap kepuasan kerja di Apotek Ating Group? (6) Seberapa besar pengaruh efikasi diri dan lingkungan kerja terhadap kepuasan kerja di Apotek Ating Group? Peneliti menggunakan metode teknik analisis frekuensi dengan menggunakan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah total jumlah karyawan berjumlah 30 karyawan. Dengan teknik pengambilan sampel menggunakan sampling jenuhs atau biasa di sebut teknik sensus yang merupakan salah satu bagian dari teknik non-probability total sampling berada di 30 responden yang berati dihitung secara keseluruhan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner, wawancara, observasi, dan studi pustaka.